2011
DOI: 10.1080/02614367.2011.589863
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and sustainable development in Norway: part of the solution and the problem

Abstract: The article presents the results of two succeeding Norwegian studies on the environmental impacts of leisure consumption. The first study presents data on the total consumption of leisure products and services by Norwegians, showing that leisure consumption increases more than everyday consumption, the most energy-intensive leisure activities increase the most, leisure activities have become more dependent on transportation and that leisure activities are to an increasing extent based on more material consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Similarly, in a study of the direct and indirect energy use associated with leisure activities by Norwegians in 2001, Aall et al (2011) found that the energy use per hour was lower for leisure activities within the home such as traditional games, and radio and television, and that activities requiring travel were in general more energy intensive per unit time. A notable exception to this was an exceptionally high energy intensity found for 'Redecoration.'…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Similarly, in a study of the direct and indirect energy use associated with leisure activities by Norwegians in 2001, Aall et al (2011) found that the energy use per hour was lower for leisure activities within the home such as traditional games, and radio and television, and that activities requiring travel were in general more energy intensive per unit time. A notable exception to this was an exceptionally high energy intensity found for 'Redecoration.'…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This idea is strongly embedded in the Norwegian tradition of outdoor recreation, as well as policy support for it [79]. The theory, or idea, that more leisure time will lead to less environmental problems, is however strongly questioned by empirical evidence [80][81][82].…”
Section: Tourism As Part Of the Solutionmentioning
confidence: 99%
“…Apart from primary dwellings, Norway has more than 423,000 holiday homes (cabins and apartments in mountain and coastal areas) with an annual growth of 5000, and almost half of Norwegians have access to a holiday home. The Norwegian holiday homes have undergone important changes including increase in size and per capita floor area, increase in technical standards, and shift from few long stays to many short stays [56]. These development trends towards spacious and luxury holiday homes will continue in future.…”
Section: Housingmentioning
confidence: 99%